Estimativas de abundância do boto-cinza (sotalia guianensis) (cetacea, delphinidae) no complexo estuarino de paranaguá utilizando modelos de captura-recaptura - Marchetto, Camila (Universidade do Vale do Rio dos Sinos, 2011)
Population abundance estimates can be considered one of the most important ecological parameters. Studies on Guiana dolphin (Sotalia guianensis) estimates are scarce and concentrated in specific areas of its distribution. The objective of the present study was to estimate the population size of this species in a sector of the Paranaguá Estuarine Complex (PEC) (25º22’S – 25º27’S; 48º12’W – 48º40’W), state of Paraná, Brazil. Surveys were conducted to apply the technique of photo-identification from winter 2006 to winter 2008. An area of 110 km² was divided into three smaller subareas to allow each selected portion of the estuary to be surveyed in a day. Boat-based surveys followed a random zig-zag pattern in the estuary in order to maximize the chance of encountering groups of dolphins. The photoidentification was performed using a 35 mm reflex digital camera with a 400 mm zoom lens. Photographs were classified into categories according to the focus, contrast and size of the dorsal fin in relation to distance from the photographer. Capture-recapture models for closed populations were used. A total of 39 surveys was conducted and 227 groups of dolphins were recorded, ranging from two to 100 individuals (mean ± SD: 12.7 ± 16.6 individuals). A total of 40.340 photographs was taken, from which 13.522 (33.5%) were considered useful for identification purposes. A total of 3.114 (23.03%) photographs allowed individual identification, resulting in 109 individuals identified through different seasons. The estimates gathered ranged from 200 to 441 individuals depending on the selected model. This is a minimum estimate, since only a part of the Paranaguá Estuarine Complex was sampled. It is recommended to survey the whole estuarine area where dolphins can be found in order to reach an accurate estimate of the total population size. This study adds another information to the database of the Environmental Protection Area of Guaraqueçaba, contributing to the development of conservation strategies of estuarine dolphins and other local biological resources.
Keywords: Sotalia guianensis; Abundância populacional; Fotoidentificação; Captura-recaptura; Population abundance; Photo-identification; ACCNPQ::Ciências Biológicas::Biologia Geral